KESIAPAN BELAJAR SISWA MENJALANI SEKOLAH LIMA HARI DI KOTA SAMPIT - Norhayatun Norhayatun; Jayadi Jayadi; Gusti Gina Ghazella Sambada (Jurnal Paedagogie Media Kependidikan, Keilmuan dan Keagamaan, 2019)
To undergo a five-day school there is a need for learning readiness from the students concerned. This research was conducted to determine the learning readiness of students undergoing five-day school in Sampit 1 Junior High School.The population in this study were students of the 8th grade 2018/2019 Middle School 1 grade, which numbered 278 students and were taken as a sample of 72 students using the Proportional Random Sampling technique. The results of quantitative descriptive analysis show that the readiness of students to undergo a five-day school in SMP Negeri 1 Sampit has a high category with a percentage of 23.61%, a medium category with a percentage of 62.50% and a low category with a percentage of 13.89%.